EVALUASI KESESUAIAN LAHAN PADA TANAH ENTISOL DI KECAMATAN LINTONG NIHUTA KABUPATEN HUMBANG HASUNDUTAN UNTUK TANAMAN KOPI ARABIKA (Coffea arabica) - Agnes Helen R. Purba; Posma Marbun; Asmarlaili Sahar Hanafiah (Jurnal Agroekoteknologi, 2013)
ABSTRACTThe purpose of the study was to find out the land suitability classes in Lintong Nihuta regency ofHumbang Hasundutan for coffee (Coffea arabica). 5 SPT (set of land) is determined by pursuant tomap of land, ground type, map of inclination of slope and map of place height yielded fromtopography map with the scale 1 : 50000, is later conducted by overlay. Assessment of landsuitability pursuant to staff criterion center the research of land of Bogor year 1983 with the limitmethod of pursuant to Djaenuddin et al. 2003. The result of analysis showed the unity of all thesample has appropriate class of land potential at SPT (set of land) 1, 2, and 4 is N (rc), class ofland potential at SPT (set of land) 3 and 5 is S3(wa,rc).